Choroba jako wynik działania czarownicy, bóstwa, demona lub ducha na przykładzie mezopotamskich tekstów magicznych i medycznych - Nicko-Stępień, Paulina (Saeculum Christianum. Pismo Historyczne, 2019)
The aim of this article is to show the influence of witches, demons, ghosts, and gods on human health in Ancient Mesopotamia. Mesopotamian medicine was based on magic and considered illness to be the work of a supernatural power. Ashu and ashipu – doctors of body and soul – worked together to diagnose and help the patient. Sometimes prayers and magical rituals were necessary for a patient to get well; often, only a herbal mixture was needed. Mesopotamian magical and medical texts describe many kinds of diseases: somatic, mental, and others. Among these are: fever, headaches, leprosy, epilepsy, blindness, impotency, paralysis. This article is an effort to analyse Mesopotamian prescriptions, incantations, and medical interventions and to answer questions about the health of ancient mankind.